ENHANCING FRAUD MITIGATION IN INDONESIAN RURAL BANKS THROUGH ORGANIZATIONAL CULTURE, INTERNAL AUDIT EFFECTIVENESS, AND GOOD CORPORATE GOVERNANCE - Fitri Ramadhan; Rita Anugerah; Hardi (Universitas Riau, 2026)
This study investigates the effects of organizational culture, internal audit effectiveness, and good corporate governance on fraud mitigation in Indonesian Rural Banks (Bank Perkreditan Rakyat/BPRs) in Riau Province. This quantitative study employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 3 to analyze data collected from 74 employees working in the finance and internal audit departments of BPRs. The findings indicate that organizational culture, internal audit effectiveness, and good corporate governance each have a positive and significant effect on fraud mitigation. The results suggest that strengthening ethical organizational values, reinforcing internal audit functions, and implementing sound governance practices can enhance fraud mitigation in rural banks. Unlike previous studies focusing primarily on commercial banks, this study provides empirical evidence from Indonesian rural banks, whose governance structures and internal control systems operate under distinct institutional and resource constraints. The findings also provide empirical support for Fraud Triangle Theory by demonstrating that organizational culture, internal audit effectiveness, and good corporate governance reduce opportunities and rationalization that contribute to fraudulent behavior.